2020
DOI: 10.1177/0300060520971508
|View full text |Cite
|
Sign up to set email alerts
|

Congenital absence of the right coronary artery with acute myocardial infarction: report of two cases and review of the literature

Abstract: Congenital absence of the right coronary artery (RCA) is a rare coronary anomaly. Few cases of this condition have been reported. Congenital absence of the RCA is considered as a benign anomaly. However, in certain cases, these patients may develop life-threatening clinical complications that include acute myocardial infarction, stroke, or sudden death. We report two patients who were diagnosed with congenital absence of the RCA and presented with acute myocardial infarction. We discuss our experience in diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Based on this literature review, several reported cases of successful PCI for MI in patients with L-I type CARCA. [ 7 , 9 , 10 , 27 , 28 ] However, there are very few cases of PCI for total occlusion of the proximal LCA in patients with this malformation. [ 7 ] This is the first reported case of PCI for total occlusion of the proximal LCX in a patient with L-I type CARCA confirmed on both CAG and coronary CTA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on this literature review, several reported cases of successful PCI for MI in patients with L-I type CARCA. [ 7 , 9 , 10 , 27 , 28 ] However, there are very few cases of PCI for total occlusion of the proximal LCA in patients with this malformation. [ 7 ] This is the first reported case of PCI for total occlusion of the proximal LCX in a patient with L-I type CARCA confirmed on both CAG and coronary CTA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 9 , 10 , 27 , 28 ] However, there are very few cases of PCI for total occlusion of the proximal LCA in patients with this malformation. [ 7 ] This is the first reported case of PCI for total occlusion of the proximal LCX in a patient with L-I type CARCA confirmed on both CAG and coronary CTA. Since CARCA is a very rare condition, various modalities should be applied to discriminate it from similar other cardiovascular malformations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations